1991
DOI: 10.1524/zkri.1991.196.14.111
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition in GaMo4S8 by X-ray powder diffraction

Abstract: GaMo4S8 transforms at T, = 45(5) K from a cubic high-temperature modification with ordered defect spinel structure (space group F43m, a = 9.7356(2) Ä at 300 K) to a rhombohedrally distorted low-temperature modification {R3m, = 6.8506(2) Ä, a^h = 60.533(1)° at 8 K). The transition is of first Order, shows a hysteresis of about 4 K, and leaves about 30% of the cubic phase untransformed. Lattice parameters as a function of temperature are reported between 8 K and 300 K, and structure refinements are performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…The amount of cubic phase estimates from the ratio of the two scale factors is greater in Π (40%) than in I (10%). The Mo -S(Se) bond distances within the pseudo-cubic Mo 4 S 4 (Se 4 ) units (marked C, in Figure 4 of Frangois et al 1991) tend to increase, and those between these units (see unit marked C 2 in Figure 4 of Francois et al 1991) tend to decrease at the cubic-to-rhombohedral phase transition. Significant structural differences between the HT and LT modifications of both compounds occur mainly with their tetrahedral MO 4 clusters.…”
Section: Rhombohedral Lt Modificationmentioning
confidence: 97%
See 1 more Smart Citation
“…The amount of cubic phase estimates from the ratio of the two scale factors is greater in Π (40%) than in I (10%). The Mo -S(Se) bond distances within the pseudo-cubic Mo 4 S 4 (Se 4 ) units (marked C, in Figure 4 of Frangois et al 1991) tend to increase, and those between these units (see unit marked C 2 in Figure 4 of Francois et al 1991) tend to decrease at the cubic-to-rhombohedral phase transition. Significant structural differences between the HT and LT modifications of both compounds occur mainly with their tetrahedral MO 4 clusters.…”
Section: Rhombohedral Lt Modificationmentioning
confidence: 97%
“…The specific-heat anomalies in these compounds indicated first-order transitions, but that in Al based II was much less pronounced than those in Ga based I and III (Ben Yaich-Aerrache, 1989). For III refined structure data at various temperatures and a study of the structural phase transition were reported by Francois et al (1991) from X-ray powder diffraction. For II non-refined data at room temperature were reported by Vandenberg and Brazen (1975) from X-ray powder diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…10 also possible that the structural phase transition is incomplete at low temperature. 7 We also find a minor trend that higher levels of functionals, as well as larger Hubbard-U values, favor larger structural distortions. Since our DFT simulations are performed at 0 K, while experimental characterizations are performed at finite temperature, our results here are more likely to capture the correct ground state structure where thermal expansion effects are small.…”
Section: Internal Degrees Of Freedommentioning
confidence: 61%
“…GaV 4 S 8 , GaV 4 S 8 , GaMo 4 S 8 , and GaMo 4 Se 8 , however, undergo symmetry-lowering structural Jahn-Teller (JT) transitions at ≈40 K from F 43m to R3m (space group no. 160), [6][7][8] followed by spontaneous magnetic ordering at a lower Curie temperature T C [Figure 1(d)]. These displacive distortions lead to a unit cell of slightly different volume, lattice parameters, and rhombohedral angle α rh .…”
Section: A Crystal Structure Electrical and Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation